2013
DOI: 10.1007/s00266-013-0227-9
|View full text |Cite
|
Sign up to set email alerts
|

The Labial Aging Process: A Surface Analysis-Based Three-Dimensional Evaluation

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
3
5
0
2
Order By: Relevance
“…This conclusion confirms the statement by Dumont who verified that skeletal classes influence soft tissue thickness, as the latter one in the chin region decreases with the increase of mandibular protrusion [24]. On the other hand, thicknesses at the upper third of the face do not significantly change as soft tissues are adherent to the bone [8].…”
Section: Discussionsupporting
confidence: 90%
“…This conclusion confirms the statement by Dumont who verified that skeletal classes influence soft tissue thickness, as the latter one in the chin region decreases with the increase of mandibular protrusion [24]. On the other hand, thicknesses at the upper third of the face do not significantly change as soft tissues are adherent to the bone [8].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, area measurements had a marginally significant time X segment interaction [19,22], while volume measurements showed a significant time X plate interaction. Apparently, the modifications in cleft segments reflect a complex three-dimensional re-organization of palatal structures, where modifications in shape and curvature should also be analyzed with suitable methods [25].…”
Section: Discussionmentioning
confidence: 99%
“…Pursuit of youthful appearance has brought increasing demand for cosmetic procedures to fight against aging 1 . The lip, holding the key aesthetic features of the lower third of the face, is heavily subjected to aging process 2,3 . Previous anthropometric studies have revealed vertical lengthening of cutaneous part of upper and lower lip, decreased height of upper and lower vermilion, and upper lip elongation 4‐6 .…”
Section: Introductionmentioning
confidence: 99%